2019
DOI: 10.3390/nano9071042
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles Mediated by Extracellular Pigment from Talaromyces purpurogenus and Their Biomedical Applications

Abstract: In recent years, green syntheses have been researched comprehensively to develop inexpensive and eco-friendly approaches for the generation of nanoparticles. In this context, plant and microbial sources are being examined to discover potential reducing agents. This study aims to utilize an extracellular pigment produced by Talaromyces purpurogenus as a prospective reducing agent to synthesize silver nanoparticles (AgNPs). Biosynthesized AgNPs were characterized by transmission electron microscopy (TEM), dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 54 publications
5
44
0
Order By: Relevance
“…4,33 Netala et al 67 reported that surface charge and small size enhanced diffusion and dispersion into the tumor matrix. Bhatnagar et al 68 showed that SNPs fabricated using extracellular pigment from Talaromyces purpurogenus have a significant cytotoxicity effect against liver cancer cell line. Abaza et al 69 showed that Cs/PVA/Ag nanocomposites caused in killing 50% of HepG2 cells at 43.7 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…4,33 Netala et al 67 reported that surface charge and small size enhanced diffusion and dispersion into the tumor matrix. Bhatnagar et al 68 showed that SNPs fabricated using extracellular pigment from Talaromyces purpurogenus have a significant cytotoxicity effect against liver cancer cell line. Abaza et al 69 showed that Cs/PVA/Ag nanocomposites caused in killing 50% of HepG2 cells at 43.7 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, silver nanoparticles (AgNPs) are of leading interest in the present scenario due to their unique physicochemical properties such as morphology structure, size distribution and surface charge, high catalytic property, high conductivity and thermal stability, and antibacterial effect [2]. In addition, their significant biomedical applications such as anticancer [3], antibacterial [4], mosquitocidal activity [5], antifungal [6], anti-inflammatory [7], anti-viral [8] have put them in the limelight in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanomaterials can be synthesized via different approaches such as physical [20], chemical [1], and biological methods [3,21]. The biological mediated synthesis of silver nanomaterials is eco-friendly, non-toxic, simple and cost-effective as compared to the physical that required high energy and pressure and chemical method involves the use of toxic reagents that are toxic to human and constituent nuisance to the environment [22].…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] are the most appropriate for extracellular production of metal NPs [26][27][28][29][30]. Thus, biosynthesis-based approaches would be attractive options if AgNP synthesis could be performed extracellularly using the extracted biomolecules present in cell-free beef extracts [29,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%